2001
DOI: 10.1046/j.1526-100x.2001.009001060.x
|View full text |Cite
|
Sign up to set email alerts
|

Restoration Ecology of an Endangered Plant Species: Establishment of New Populations of Cirsium pitcheri

Abstract: We determined the effects of shade, burial by sand, simulated herbivory, and fertilizers on the survival and growth of artificially planted population of Cirsium pitcheri -an endangered plant species of the sand dunes along Lake Huron. Sand burial experiments showed that greenhouse grown plants should optimally be transplanted into areas receiving 5 cm of sand deposition: burial at this depth maximized emergence, survivorship, and below-ground biomass. Under field conditions, simulated herbivory of up to 50% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 24 publications
3
18
0
Order By: Relevance
“…Decreased light levels and the presence of litter reduced seedling emergence of C. pitcheri by 14-34% in our growth chamber experiment. These results corroborate those of Rowland and Maun (2001) who showed that C. pitcheri germination and seedling vigor are reduced by shade in the field. The negative impact of shade on plant survival and growth has been shown for other monocarpic perennials (Gross, 1984) and Lake Michigan dune taxa (Lichter, 2000).…”
Section: Population-level Effects From Seedling Response To Shade Andsupporting
confidence: 91%
See 1 more Smart Citation
“…Decreased light levels and the presence of litter reduced seedling emergence of C. pitcheri by 14-34% in our growth chamber experiment. These results corroborate those of Rowland and Maun (2001) who showed that C. pitcheri germination and seedling vigor are reduced by shade in the field. The negative impact of shade on plant survival and growth has been shown for other monocarpic perennials (Gross, 1984) and Lake Michigan dune taxa (Lichter, 2000).…”
Section: Population-level Effects From Seedling Response To Shade Andsupporting
confidence: 91%
“…We expressed F ij fecundity for C. pitcheri as a measure of seedling recruitment, defined as the number of seedlings per reproductive plant in the previous year (F 14 = n (seedling, t+1) /n (adult, t) ). Pitcher's thistle lacks a significant seed bank (Rowland and Maun, 2001); thus, this transition was not included as part of our demographic modeling. We also constructed ternary diagrams to compare the WSP population to other reports for C. pitcheri populations and related species (Silvertown et al, 1996;Bell et al, 2003).…”
Section: Population Viability Model Assumptions and Parametersmentioning
confidence: 99%
“…In an experiment about the factors affecting seedling survival, Carol found that shade conditions affected early survival, and the death of seedlings of six species in nine species contributed to pathogens infection [40]. To ensure that rare and threatened flora extinctions be prevented or at least minimized, numerous attempts have been made to create new populations of endangered plants by translocation [41,42]. A successful translocation can be defined by addressing four goals of abundance, extent, resilience and persistence [43].…”
Section: Discussionmentioning
confidence: 99%
“…obs.). It appears to have a very short-lived seed bank (Loveless, 1984;McEachern, 1992;Bowles and McBride, 1996;Hamzé and Jolls, 2000), which is unlikely to contribute significantly to population growth (Rowland and Maun, 2001).…”
Section: Study Speciesmentioning
confidence: 99%